Comparative and systems analyses of Leishmania spp. non-coding RNAs through developmental stages. - J Eduardo Martinez-Hernandez; Victor Aliaga-Tobar; Carolina González-Rosales; Rubens Monte-Neto; Alberto J M Martin; Vinicius Maracaja-Coutinho (PLoS Neglected Tropical Diseases)
Leishmania spp. is the etiological agent of leishmaniases, neglected diseases that seek to be eradicated in the coming years. The life cycle of these parasites involves different host and stress environments. In recent years, many studies have shown that several protein-coding genes are directly involved with the development and host interactions. However, little is still known about the role of non-coding RNAs (ncRNAs) in life cycle progression. In this study, we aimed to identify the genomic structure and function of ncRNAs from Leishmania spp. and to get insights into the repertoire of ncRNAs (RNAome) of this protozoan genus. We studied 26 strains corresponding to 16 different species of Leishmania. Our RNAome analysis revealed the presence of several ncRNAs that are shared among different species, allowing us to differentiate between subgenera as well as between species that are canonically related to visceral leishmaniasis. We also studied co-expression relationships between coding genes and ncRNAs which in the amastigote developmental stage for Leishmania braziliensis and Leishmania donovani revealed the presence of miRNA-like transcripts co-expressed with several coding genes involved in starvation, survival and histone modification. This work represents the first effort to characterize the Leishmania ssp. RNAome, supporting further approaches to better understand the role of ncRNAs in gene regulation, infective process, and host-parasite interaction.